A mitopráxis policial: uma explicação cibernética da guerra contra o bandido - SANTOS, Vinícius Barriga dos (UNIFAP – Universidade Federal do Amapá, 2022)
The objective of this monograph is to describe, via ethnography, the symbolic system, propagated regionally by the police-media-population cybernetic circuit, which makes possible the interpretative scheme of the discourses that support police lethality, responsible for its effectiveness and its reproduction from the popular support. Understood as a social mechanism for legitimizing police violence practices, this discourse extracts its significant contents from the Macapá social context and from the symbolic reference and/or rationality of the police institution itself - founded around an emic construction of the criminal and the war logic against the intern enemy. In conducting the research, I chose to analyze the aforementioned symbolic system from the police perspective, since the police injects into the local cybernetic circuit the interpretive categories that animate the discourse of support for police lethality, enabling feedback from the systemic media-population parties, the dynamics of this circuit re-circulates contents generated primarily by the police for the police, producing the effects of legitimation in a recursive way. Starting from the methodological scope based on an ethnographic digital anthropology and on the batesonian cybernetics, the ethnographic field is located on the Devotos do BOPE-AP page on Facebook. Being managed by the police themselves, the page gathers, via an algorithmic system, in a concentrated way, the discursive manifestations of support for police lethality that otherwise would be dispersed in the mix of the social fabric, constituting itself as a strategic field to visualize the constitution of the symbolic system that makes the slaughter promoted by the State of Amapá socially acceptable. We apply the hidden observation research technique that allows us to capture native categories in the flow of the digital platform without contacting internet users, just observing them in their mutual online interactions. The reconstruction of the symbolic system took place from the capture of the categories that the page's followers, the police and the media use to address issues related to violence and police incidents.